PERTANGGUNG JAWABAN PEJABAT PEMERINTAH AKIBAT TERJADINYA MALADMINISTRASI DALAM PELAYANAN PUBLIK - Ryo Martin Sopian; Annisha Amalia, Zainab Ompu Jainah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The concept of a welfare state upholds the existence of a legal system that guarantees legal certainty and protection of the basic rights of the people. This is in line with the Preamble to the 1945 Constitution paragraph IV which states: "then rather than that to form a Government of the State of Indonesia that protects the entire Indonesian nation and all Indonesian bloodshed and to promote the general welfare" From this foundation it emphasizes the existence of "state obligations" and "government duties" to protect and serve all public interests. The mandate of the 1945 Constitution regarding public services is outlined in Law Number 25 of 2009 concerning Public Services. The government or government administration is a subject of law and as a supporter of the rights and obligations to carry out various actions, both real and legal. Law Number 30 of 2014 concerning Government Administration explains that Government Administrative Actions, hereinafter referred to as actions, are the actions of government officials or other state administrators to do and/or not commit concrete acts in the context of government administration. One of the requirements for the validity of government administrative actions is the existence of authority. In accordance with the principle of "geen bevoegdheid zonder verantwoordelijkheid" which means no authority, no accountability. In principle, the obligation to bear responsibility by the government is the function of returning to the condition before the violation of the law. However, if the return effort fails, as a consequence the government's liability is burdened with the obligation to compensate. The main problem that occurs in the implementation of public services is the orientation of public service performance. Orientation in the implementation of services gives birth to a bureaucratic culture. The culture of bureaucracy in the service that has long been a disease is the habit of bureaucrats who ask to be served rather than serve. Conditions like this are the main element of maladministration. If government officials in the use of government authority there are elements of abuse of authority (detournement de pouvoir) and arbitrary actions (abuse de droit), then there is an element of maladministration and of course there is an element of unlawful acts. So that officials who commit maladministration will be held accountable for the act.